Neurological Symptoms of COVID-19: The Zonulin Hypothesis - Llorens, Sílvia; Nava, Eduardo; Muñoz-López, Mónica; Sánchez-Larsen, Álvaro; Segura, Tomás (Frontiers in Immunology, 2021)
The irruption of SARS-CoV-2 during 2020 has been of pandemic proportions due to its rapid spread and virulence. COVID-19 patients experience respiratory, digestive and neurological symptoms. Distinctive symptom as anosmia, suggests a potential neurotropism of this virus. We postulate an alternative pathway of entry to the brain from the infection of the gut, involving Toll-like receptor 4 (TLR4), the zonulin, the protease-activated receptor 2 (PAR2) and the zonulin brain receptor. Possible use of zonulin antagonists could be investigated to attenuate neurological manifestations caused by SARS-CoV-19 infection.